The relationship between cyber upward social comparison and cyberbullying behaviors: A moderated mediating model - Wen, Hong; Kong, Xiangwei; Feng, Yonggang (Frontiers in Psychology, 2022)
Based on the General Strain Theory (GST) and the moderating role model of social support, the present study explored the relationship between cyber upward social comparison and cyberbullying and further explored the mediating role of moral justification and the moderating role of online social support. This model was examined with 660 Chinese college students. Participants completed questionnaires regarding cyber upward social comparison, cyberbullying, moral justification, and online social support. After basic demographic variables were controlled, cyber upward social comparison was significantly and positively associated with cyberbullying. Moral justification played a mediating role in the relationship between cyber upward social comparison and cyberbullying. The mediating effect of moral justification on the relationship between cyber upward social comparison and cyberbullying was moderated by online social support. The results of this study will provide references for the prevention and intervention of cyberbullying.